Decision published pursuant to Article 14(8) of the Gas (Northern Ireland) Order 1996 : Modification of Gas Conveyance Licences - Postalised Transmission Tariff Published Prior to 31 May : Decision Paper.: Modification of Gas Conveyance Licences - Postalised Transmission Tariff Published Prior to 31 May : Decision Paper. (2017) - Northern Ireland., Utility Regulator,
No abstract available